Hematological and biochemical disturbances caused by Brucella ovis infection using an experimental model - Perin G.* (2018)
© 2018, Springer-Verlag London Ltd., part of Springer Nature.Ovine brucellosis is an infectious disease caused by Brucella ovis, a Gram-negative bacterium associated with high economic losses in consequence of fertility impairment and commercial restrictions. In this sense, it is important to emphasize that the pathological mechanisms of B. ovis infection are poorly understood, since the euthanasia of affected animals is recommended. Thus, the aim of this study was to evaluate hematological and biochemical disturbances caused by this microorganism using mice as the experimental model. In this way, 48 animals were divided into two groups: uninfected (control) and infected. Hematocrit, leucogram, serum biochemistry (total protein, albumin, globulin, and glucose), reactive oxygen species (ROS), and histopathology of the liver and spleen was evaluated on days 7, 15, 30, and 60 post-infection (PI). Hematocrit of infected animals was lower than the control group on days 7, 15, and 30 PI, while leukocyte counts were higher as a consequence of increased lymphocytes, neutrophils, and monocytes in some periods of the infection. Serum albumin levels were lower in infected animals compared to the control group in all evaluated periods, while serum glucose levels were lower on days 7 and 60 PI. On the other hand, serum globulin levels were higher in infected animals compared to that in the control group on days 15, 30, and 60 PI. Moreover, spleens of infected mice were severely enlarged, as well as increased levels of splenic and hepatic reactive oxygen species in various periods of infection as hematological and biochemical disturbances caused by B. ovis infection using a novel experimental model consequence of granulomatous splenitis and multifocal hepatic granuloma. Based on these results, we concluded that B. ovis infection can cause disorders related to the inflammatory response and exacerbation of free radicals linked to tissue lesions, which can be directly associated to a decrease in serum levels of albumin and glucose.